Special Issues Encountered When Cancer Patients Confront COVID-19 - Qi, Lina; Wang, Kailai; Ye, Chenyang; Zheng, Shu (Frontiers in Oncology, 2020)
Since the beginning of the COVID-19 global pandemic, there has been insufficient evidence and experience to help oncologists understand how to deal with infected and noninfected cancer patients. Many hospitals worldwide have shared their experiences of managing such patients by using the internet to reach noninfected cancer patients. However, for infected or suspected infected cancer patients, their experiences in terms COVID-19 diagnosis, anticancer treatment and prognosis are largely unknown and controversial. Here, we summarize the incidence, severe illness rate and mortality according to the published clinical data of COVID-19 in cancer patients and discuss the diagnostic difficulties, anticancer treatment and prognosis of COVID-19-infected cancer patients.